Conference on Lasers and Electro-Optics 2022
DOI: 10.1364/cleo_at.2022.jth3b.26
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-optical transduction using high overtone bulk acoustic resonances

Abstract: We demonstrate efficient microwave-optical frequency conversion using a released HBAR-on-photonic damascene platform. Thermal tuning of coupled optical ring cavities with integrated heaters allows to operate in the triply resonant transduction scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Transducers mediated by BAR exhibit structural flexibility and have several demonstrated advantages, including high-frequency acoustic mode, low cooling requirements, and high bandwidth [39,91]. Furthermore, by selecting different piezoelectric materials and optimizing the structure (such as using a thinner optical waveguide), significant improvements in parameter values may be achieved, rendering them worthy of further research [39,91].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transducers mediated by BAR exhibit structural flexibility and have several demonstrated advantages, including high-frequency acoustic mode, low cooling requirements, and high bandwidth [39,91]. Furthermore, by selecting different piezoelectric materials and optimizing the structure (such as using a thinner optical waveguide), significant improvements in parameter values may be achieved, rendering them worthy of further research [39,91].…”
Section: Discussionmentioning
confidence: 99%
“…As depicted in Figure 6b, this structure has been used in the modular design of piezoelectric optomechanical systems, achieving both piezoelectric and Brillouin coupling in x-cut quartz, thus accomplishing bi-directional microwave-optical conversion with conversion efficiencies up to 10 −8 at C om exceeding one [39]. Blesin et al's [91] recent work has demonstrated significant progress, achieving a bandwidth of 25 MHz and a conversion efficiency of 1.6 × 10 −5 at room temperature. Moreover, they were able to generate nonclassical correlated microwave-optical photon pairs.…”
Section: Bulk Acoustic Wave Resonator (Bar)mentioning
confidence: 99%
See 1 more Smart Citation